PERSEPSI ORANG TUA SISWA TENTANG GEOGRAFI SEBAGAI MATA PELAJARAN DI SMA DAN MA NEGERI DI KOTA SUNGAI PENUH - Ikhwanul Furqon; ernawati erna; ratna willis (JURUSAN GEOGRAFI FIS UNP, 2017)
Aims of this sutdy is to understand how Parents peerception of geography as a subject in state SMA and MA in Sungai Penuh City. This research is descriptive quantitative with survey method, using questionnaire as research instrument. Subject of this research is Parents of Students in State SMA and MA in Sungai Penuh City which is 1415 parents, and sample about 93 parents. Data analysis using descriptive statistic with persentage. Result of this research shows that parents perception about role of geography knowledge in a proffesion is not good with persentage 38,71%, parents perception about role of geography subject in attitude thoward environmental care is good with persentage 32,26%, parents perception about role of geography knowledge about global issues is quite good with persentage 49,46%, and parents perception about geography study in SMA/MA is quite good with persentage 33,33%.